Determinants of Firm Value: A Study on Islamic Banking in Indonesia - Mochammad Ridwan; Erik Syawal Alghifari; Winwin Yadiati; Karisma Azahra Hidayah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This study attempts to measure the effect of Islamic corporate governance (ICG) and Islamic social responsibility (ISC) on firm value and to analyse the moderation role of profitability. Data from 12 Islamic commercial banks registered in Indonesia were taken from 2017 to 2021 and analyzed using a panel data regression approach with the GLS approach and model robustness testing using the robust least squares analysis method. The results of this study show a positive effect of ICG on firm value and a negative effect of ISC on firm value. The moderation results show that the interaction between profitability and ICG further strengthens the ICG effect on firm value. The results also reveal a negative effect of profitability on the effect of ISC on firm value. This paper discusses the implications of this research for the existing literature, practitioners, and policymakers.